PERANAN IBU DALAM PEMBINAAN KEPRIBADI ANANAK (Journal Ilmu Sosial, Politik dan Pemerintahan, 2013)
The research was conducted with the aim to study the role of the mother in the child's personality development. Mother as the figure closest to the child have an interesting relationship dynamics with his son. The subjects were randomly selected mothers. This research method uses descriptive quantitative methods of data collection techniques by using questionnaires and interviews. The results is described descriptively. The conclusion can be drawn that the mother has been carrying out the role of the child's personality development quite well although it is still unknown mother's ability to master his feelings in the implementation of discipline in children still need to be reviewed and the persistence of giving labels in children's personality development to enable the child to be less than the maximum.